A descriptive analysis of arglicism used in Ecuadorian magazines - Rodríguez Herrera, Santiago David (2012)
This thesis is a valued sum to the knowledge of the anglicisms in our era due to the increasing use of the native English words in Spanish found in Ecuadorian magazines. The process of investigating was a little bit hard because I had to research the information in 2 libraries in Guayaquil either the internet or the books at home. One of those libraries is in UEES and the other is in the municipality of Guayaquil. I used 2 magazines per variable so those variables are scholarly, general interest, and cultural ones. In the scholarly magazines I employ the PC Ecuador but in the cultural ones I made use of El Búho and La Casa de la Cultura magazine and then I use Vistazo in the general interest ones. The methods I used were qualitative and quantitative and the qualitative research produces the hypotheses and the quantitative research will confirm if those guesses are true. The obtained results show that the anglicisms related to technology are the most used yet therefore the conclusions are that if people get in touch with technology they will use more anglicisms.